Yeast Cell-Based Transport Assay for the Functional Characterization of Human 4F2hc-LAT1 and ‐LAT2, and LAT1 and LAT2 Substrates and Inhibitors - Kantipudi, Satish; Fotiadis, Dimitrios (Frontiers in Molecular Biosciences, 2021)
In mammalian cells, the L-type amino acid transporters (LATs) LAT1 (SLC7A5) and LAT2 (SLC7A8) form heterodimeric amino acid transporters (HATs) with the ancillary protein 4F2hc and are involved in the cellular uptake of specific amino acids. The HAT 4F2hc-LAT1 is found upregulated in various cancer cell types, while 4F2hc-LAT2 is a transporter for non-cancer cells. Preclinical studies have highlighted that 4F2hc-LAT1 plays an important role in tumor progression representing a valid anticancer target. Consequently, current research is focusing on the development of potent and specific human 4F2hc-LAT1 inhibitors. On the other hand, 4F2hc-LAT2 is emerging as target of other diseases, thus also gaining clinical interest. To determine affinity and specificity of substrates and inhibitors for 4F2hc-LAT1 or 4F2hc-LAT2, robust transport cell assays are indispensable. We have optimized and validated a transport assay using cells of the methylotrophic yeast Pichia pastoris stably overexpressing the human HATs 4F2hc-LAT1 or -LAT2, and the LATs LAT1 or LAT2 alone. The radioligand [3H]L-leucine was used as reporter and the substrates L-leucine, triiodothyronine (T3) and thyroxine (T4) as well as the inhibitors BCH and JPH203 (KYT-0353) for assay validation. Obtained half-maximal inhibitory concentrations also provided new insights, e.g., into the LAT specificity of the potent inhibitor JPH203 and on the potency of the thyroid hormones T3 and T4 to inhibit transport through human 4F2hc-LAT2. The LAT1 and LAT2 assays are of particular interest to determine possible implications and influences of 4F2hc in ligand binding and transport. In summary, the presented assays are valuable for characterization of ligands, e.g., towards 4F2hc-LAT1 specificity, and can also be applied for compound screening. Finally, our established approach and assay would also be applicable to other HATs and LATs of interest.